1996
DOI: 10.1001/archpsyc.1996.01830110037005
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind, Placebo-Controlled Study of Fluvoxamine in Adults With Autistic Disorder

Abstract: Fluvoxamine is more effective than placebo in the short-term treatment of the symptoms of autistic disorder in adults. Controlled studies of fluvoxamine and other potent and selective serotonin uptake inhibitors seem warranted in children and adolescents with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
243
2
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 505 publications
(255 citation statements)
references
References 49 publications
6
243
2
4
Order By: Relevance
“…This suggests that the effect may be clinically meaningful. However, prior findings in adults with autism with fluvoxamine (McDougle et al, 1996b) and clomipramine (Gordon et al, 1993) were even more robust, showing statistical separation in parallel design studies of similar sample size, whereas our study did not reach statistical significance in a post hoc comparison of the first phase only. Since this study was conducted with children and adolescents, dosing levels were kept low, and were thus much lower than doses typically used in adult trials.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This suggests that the effect may be clinically meaningful. However, prior findings in adults with autism with fluvoxamine (McDougle et al, 1996b) and clomipramine (Gordon et al, 1993) were even more robust, showing statistical separation in parallel design studies of similar sample size, whereas our study did not reach statistical significance in a post hoc comparison of the first phase only. Since this study was conducted with children and adolescents, dosing levels were kept low, and were thus much lower than doses typically used in adult trials.…”
Section: Discussioncontrasting
confidence: 89%
“…In the only double-blind study of an SSRI in adult autism to date, McDougle et al (1996b) conducted a placebo-controlled study of fluvoxamine and found that 8/15 (53%) patients were responders compared to 0/15 in the placebo group. Significant improvements in repetitive thoughts and behavior, maladaptive behavior, aggression, social relatedness and language usage were reported.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous hypotheses, the results of our study suggest that serotonergic mechanisms may play a role in the pathophysiology of autism. As described in the Introduction, evidence that the serotonergic system is involved in the pathophysiology of autism comes from pharmacological studies with SSRIs (McDougle et al 1996a), behavioral research, such as results of tryptophan depletion techniques (McDougle et al 1996b), molecular biology (Cook and Leventhal 1996;Cook et al 1997) and brain imaging (Chugani et al 1997(Chugani et al , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Selective 5-HT reuptake inhibitors (SSRIs), have beneficial effects in the treatment of some individuals with autism (McDougle et al 1996a). Tryptophan depletion techniques result in a significant increase in autistic behaviours (McDougle et al 1996b). PET-scan studies revealed decreased 5-HT synthesis in frontal cortex and thalamus, but elevated 5-HT synthesis in the contra-lateral dentate nucleus (Chugani et al 1997).…”
Section: Serotonin (5-ht)mentioning
confidence: 99%
“…Higher prevalence of autistic traits has been found in OCD samples both in adults [5,6] and children [16], and some evidence suggests that treatments effective for OCD may be effective for repetitive thoughts and behaviours in ASD as well [15,19,24,25]. Also, family studies have reported an association between restrictive or repetitive behaviours in probands with autism and obsessive-compulsive features in parents both in multiplex [14] and sporadic autism families [1].…”
Section: Introductionmentioning
confidence: 99%